Sputnik's guide to life on Earth - Cottrell Boyce, Frank (Walden Pond Press, an imprint of HarperCollins Publishers, 2017)
Separated from his grandfather and placed in a foster home, Prez forges a friendship with an alien who appears as a dog to everyone else and entreats Prez to help compile a list of Earth's redeeming qualities.